Profile of the nutritional intake of patients with decreased bone mass - Gisele Mariana do Nascimento Schiavo; Eliege Carolina Vaz; Michele Novaes Ravelli; Kamila Assis Kihara; Carolina Magrin Saullo; José Eduardo Corrente; Célia Regina Nogueira; Gláucia Maria Ferreira da Silva Mazeto (Revista Ciência em Extensão, 2014)
Osteoporosis is a systemic disorder in which there is bone fragility and an increase in susceptibility to fractures. A balanced diet that provides sufficient quantities of proteins, vitamins, and minerals has a positive influence on bone health. The aim of this study was to determine the profile of consumption of the main nutrients involved in bone health, in order to optimize their ingestion, in patients with low bone mass. The progress of the patients was followed at the calcium disorders outpatients unit of the Clinical Hospital of Botucatu Medical School (UNESP). Forty-five patients with low bone mass were invited to participate in this study. Of these, 15 women, with an average age of 60.7 years, accepted and concluded the project. 24-h food recollections were performed and nutritional education activities (NEA) were organized based on an information leaflet, with the aim of optimizing the consumption of calcium (Ca), vitamin D, phosphorus (P), magnesium (Mg), and other nutrients involved in bone health. There was also tasting of dietary preparations rich in Ca. The average consumption of the nutrients was evaluated before and after the end of the activities, using the program DietPro 5i®. The median ingestion of energy (1096.8 Kcal) and macronutrients (carbohydrates: 127.2 g; proteins: 40.4 g; lipids: 20.4 g) was below the levels recommended according to the Dietary Reference Intakes (DRI). The consumption of energy and the nutrients showed no significant changes after the NEA (energy: 1120.8 Kcal; carbohydrates: 164.8 g; proteins: 60.5 g; lipids: 29.9 g; p>0.05). The median ingestion of micronutrients was also below the levels recommended by DRI/Institute of Medicine (IOM) (Ca: 661.57 mg; vitamin D: 0.64 µg; Mg: 292.71 mg; P: 1214.00 mg). The consumption of such nutrients did not present significant changes after the NEA (Ca: 619.57 mg; vitamin D: 0.73 µg; Mg: 212.15 mg; P: 821.24 mg; p>0.05). The percentage deficiencies for Ca, vitamin D and Mg were elevated (81.7%, 99.8%, and 100%, respectively). The percentage deficiency for P was 36%. In this group of female patients with low bone mass, there was an unsatisfactory ingestion profile for the main nutrients related to bone health. The nutritional guidance provided during the 8-month period was not effective in optimizing such ingestion. This finding highlights the importance of establishing new strategies in order to optimize the consumption of these nutrients.